Uma Análise sobre o consumo atual de drogas - Morales, Lúcia Arrais [UNESP] (My University, 2012)
The article analyses some characteristics of drug consumption at this moment. Two sources of data are used: interviews made, between 2005 and 2008, with addicts and two narratives about drugs, released by the published market (Arti cial Paradise by Charles Baudelaire and !e Last Opium Dem by Nick Tosches). Two concepts are priorized: boredom and insu"ciency vexatious. By them, the article shows that nowadays capitalism dynamic, centred in the continuous production of past devaluation and in the impulse toward a triumphant competitivity, it is impoverishing coletive life and it is spreading out on a large scale the use of psicoactive substances.

O artigo analisa algumas das características atuais do consumo de drogas. Duas fontes de dados são usadas: entrevistas realizadas, entre 2005 e 2008, com dependentes químicos e dois relatos sobre a questão das drogas, publicados pelo mercado editorial (Paraísos Arti ciais de Charles Baudelaire e A última Casa de Ópio de Nick Tosches). Dois conceitos são priorizados: tédio e insu ciência vexaminosa. Através deles, demonstra-se que a atual dinâmica do individualismo, centrada na produção contínua do desvalor ao passado e no impulso para uma competitividade triunfante, está empobrecendo a vida coletiva e fazendo expandir em larga escala o uso de substâncias psicoativas.
An analysis about the nowadays drug consumption